1996
DOI: 10.1152/ajpheart.1996.271.1.h303
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal heart rate variability in healthy subjects: effects of aging and sex difference

Abstract: To study the effects of aging and gender, circadian profiles of heart rate variability were evaluated for 105 healthy volunteers by frequency domain analysis of a Holter electrocardiogram record. The low-frequency (LF) component representing cardiac beta-adrenergic function showed high values for the 0800-1200 period in male subjects and the 1200-2400 period in female subjects. The high-frequency (HF) component representing parasympathetic function showed a peak for the 0000-0600 period in both male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 0 publications
11
58
1
2
Order By: Relevance
“…These findings may reflect circadian variations in the autonomic nervous system and HRV [50] and are consistent with past findings of decreasing HRV parameters over the day [12,24].…”
Section: Resultssupporting
confidence: 92%
“…These findings may reflect circadian variations in the autonomic nervous system and HRV [50] and are consistent with past findings of decreasing HRV parameters over the day [12,24].…”
Section: Resultssupporting
confidence: 92%
“…showed that female gender was an independent predictor of non-pulmonary vein ectopic beats at multivariable analysis. 22 The authors speculated that female hormones might play a role in the higher incidence of superior vena cava ectopic beats in women and that the higher parasympathetic autonomic tone of women 23,24 might account for the higher incidence of superior vena cava site of ectopic beats initiating AF, due to the proximity of autonomic nerves and ganglionated plexi to the superior vena cava. 22 With regard to procedure-related complications, females might experience increased rates of adverse events.…”
Section: Catheter Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…Additionally, our study population was only male, although a sex difference in HRV has been reported. 11,23) Therefore, the variation in the 5-minute measurement was large and unstable.…”
Section: Discussionmentioning
confidence: 99%